Buyer-Supplier Partnerships within IT Purchasing A case study at Volvo Group - Nilsson, Jonathan; Odbratt, Marcus (My University, 2023)
The role of the purchasing division has changed over time, moving from an administrative function to a strategic one. How a buyer manages its suppliers can greatly impact the performance of the company. Supplier management have moved from putting the suppliers at an arm’s length distance to interacting closer with selected suppliers. Volvo Digital & IT are looking to develop how they work with their suppliers, and especially with partnerships. To investigate the topic of partnerships within IT services, a thesis based on semi-structured interviews and observations were carried out at Volvo Group and with some of their strategic suppliers. The results shows that the current way of working can be beneficial in a partnership relationship, however there are some areas where changes could be made. Improved internal alignment, increased risk-sharing, and a precise definition of what a partnership is, are areas of improvement.
Keywords: Buyer-supplier relationships; Partnerships; Strategic partnerships; Performance-based contracting; Supplier risk management; IT services